2007
DOI: 10.1016/j.pain.2007.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of central cyclooxygenase (COX) pathways enhances the cannabinoid-induced antinociceptive effects on inflammatory temporomandibular joint (TMJ) nociception

Abstract: The present study is the first to investigate the participation of central cyclooxygenase (COX) pathways in modulating the antinociceptive effects of intracisternally administered cannabinoid on nociception induced by inflammation of the temporomandibular joint (TMJ) in freely moving rats. Following intra-articular injection of 5% formalin in the TMJ, nociceptive scratching behavior was recorded for nine successive 5-min intervals in Sprague-Dawley rats. Intracisternal injection of 30 microg of WIN 55,212-2, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 51 publications
1
39
0
2
Order By: Relevance
“…The analgesic activity of acetaminophen in rats can be completely prevented by addition of a cannabinoid (CB1) receptor antagonist (27,28). Blockade of central COX pathways can enhance a cannabinoidinduced antinociceptive effect (29).…”
Section: Discussionmentioning
confidence: 99%
“…The analgesic activity of acetaminophen in rats can be completely prevented by addition of a cannabinoid (CB1) receptor antagonist (27,28). Blockade of central COX pathways can enhance a cannabinoidinduced antinociceptive effect (29).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that spinal COX2 was activated and was involved in driving the initial hyperalgesia and allodynia following peripheral tissue injury (Ghilardi et al, 2004), and indomethacin (a nonselective COX inhibitor) could reduce spinal nociception during the formalin test (Yamamoto and Nozaki-Taguchi, 1996). Recent studies also found that central COX2 pathways participated in the IL-1b-induced hyperalgesia and cannabinoids modulated antinociception in the orofacial formalin test (Choi et al, 2003;Ahn et al, 2007). Furthermore, a recent study showed that conditional deletion of COX2 gene in central nervous system could inhibit the development of inflammatory mechanical allodynia (Vardeh et al, 2009).…”
Section: Cox2 and Orthodontic Painmentioning
confidence: 99%
“…Intrathecal administration of COX2 inhibitors was reported to decrease inflammation-induced PGE2 levels in the spinal cord of rats (Samad et al, 2001). Recently, it was found that central COX2 pathway played an important role in the IL-1b-induced hyperalgesia in the orofacial formalin test (Choi et al, 2003) and modulated the antinociceptive effects of cannabinoids in the formalin-induced temporomandibular joint nociception (Ahn et al, 2007). Furthermore, a recent study also showed that COX2 expressed within spinal dorsal horn neurons played an essential role in the development of inflammatory mechanical allodynia by increasing neuronal excitation (Vardeh et al, 2009).…”
mentioning
confidence: 99%
“…AM404 inhibits the cellular uptake of anandamide, an endocannabinoid, and is an agonist at the vanilloid receptor TRPV1, which is believed to play a central role in nociception. The analgesic activity of paracetamol in rats can be completely prevented by addition of a CB 1 receptor antagonist [34,35], while blockade of central COX pathways can enhance a cannabinoid-induced antinociceptive effect [36].…”
Section: Mechanism Of Actionmentioning
confidence: 99%